Thickness-controlled metal nanoscale etch for proposed metal nanowires fabrication - Lee, B.C.; Kim, M.H.; Shin, H.J.; Moon, S. (2007 NSTI Nanotechnology Conference and Trade Show - NSTI Nanotech 2007, Technical Proceedings, 2007)
A novel nanoscale etch process of metallic structures, the metal peel-off method(MPOM), is developed. The etching area can be defined photolithographically on the exposed substrate. Utilizing galvanic displacement as well as selective etching process after photolithographic process, we simply and uniformly achieve self-controlled etch rate of 32.2±2.1nm/times through whole wafer level. MPOM provides a high throughput and low temperature etching process which is compatible with conventional semiconductor process. We also propose a novel top-down fabrication process, from the MPOM to the metal peel-off lithography(MPOL) for the patterning and formation of metal nanowires.